1994
DOI: 10.1038/sc.1994.128
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the venous vascular system in the lower extremities of individuals with paraplegia

Abstract: The purpose of this study was to examine the properties of the venous vascular system in the lower extremities of individuals with long-standing paraplegia (PP). The venous volume variations (VVV) , the venous capacity (VC), the venous emptying rate (VER) and the venous flow resistance (VFR) were measured in the left calf of 14 male PP and 12 male able-bodied subjects (ABS) by means of strain-gauge occlusion plethysmography. VVV and VC were significantly lower in PP compared to ABS, -45% and -50% respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 18 publications
7
60
1
3
Order By: Relevance
“…Phenotyping of osteoclasts in HO revealed their derivation from mature local macrophages and expression intensities of the proliferation markers PCNA and MIB1 suggested a proliferation behavior in peripheral areas of osteogenesis similar to that found in autonomous osseous neoplasias and underlined the reactive-proliferative character of HO. 12 Prostaglandins and other eicosanoids have been shown to have a role in bone metabolism and to induce HO in experimental animals. Furthermore, elevation of urinary prostaglandin E2 has been demonstrated to herald the formation of HO.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotyping of osteoclasts in HO revealed their derivation from mature local macrophages and expression intensities of the proliferation markers PCNA and MIB1 suggested a proliferation behavior in peripheral areas of osteogenesis similar to that found in autonomous osseous neoplasias and underlined the reactive-proliferative character of HO. 12 Prostaglandins and other eicosanoids have been shown to have a role in bone metabolism and to induce HO in experimental animals. Furthermore, elevation of urinary prostaglandin E2 has been demonstrated to herald the formation of HO.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study we observed the highest muscle T 2 values in wheelchair users (S5, S6, S7 and S8). As persons with motor incomplete SCI have vascular disturbances including venous vascular dysfunction, 18 a continuous dependent position of their lower extremities (in the seated position) most likely leads to accumulation of myocellular water in the postural leg muscles.…”
Section: Incomplete Sci (Ambulatory)mentioning
confidence: 99%
“…Using venous occlusion plethysmography, and in contrast to the comparable LF SBP ®ndings, investigators have reported signi®cantly reduced venous vascular function below the level of injury in subjects with tetraplegia or paraplegia relative to able-bodied controls (0.34+ 0.11 or 0.51+0.21% vs 0.255+0.92% respectively; P50.05). 186,191 Venous compliance, a measure of the responsiveness of the vascular system, was approximately ®vefold lower in the SCI groups than controls, indicating that the combination of autonomic disruption, immobility and inactivity caused considerable reduction in vessel compliance and responsiveness. The clinical implications of these ®ndings suggest that orthostatic intervention and/or regular physical activity may improve vascular integrity and, potentially, peripheral and central venous pressure in individuals with SCI.…”
Section: Peripheral Vascular Functionmentioning
confidence: 99%